Comparison of Consumer Perceptions of the Marketing Mix at the Indomaret Minimarket with the Alfamart Minimarket in Pagar Alam City - Baheramsyah Baheramsyah; Novriansyah Novriansyah (Penerbit Jurnal Indonesia, 2021)
This study examines the ratio of consumer perceptions of Price, Product, Promotion and Place at the Indomaret Minimarket and Alfamart Minimarket in Pagar Alam City. This research is a comparative research. To determine the respondents using accidential sampling, while the number of respondents in this study were 100 respondents. The data collection method used consists of the following methods: Questionnaire and documentation. Meanwhile, to find out the relationship between the variables the author uses the method of calculating validity, reliability, and the sample of respondents using the SPSS 16.0 analysis tool. The results showed that the difference in price, product, promotion and place by respondents to the Indomaret Minimarket and Alfamart Minimarket in Pagar Alam